Markers of Economic Modernization and the Overexploitation of Fish Stocks - Zanette, Eric (Université d'Ottawa | University of Ottawa, 2020)
This paper investigates how the levels of trade openness, credit market access and the strength of property rights affect the level of overfishing within a state’s Exclusive Economic Zone. A comparison is made between Erhardt (2018), who explores how overfishing is affected by trade openness and strength of property rights, and Noack and Costello (2019), who explore how overfishing is affected by access to credit markets and the strength of property rights. We use a dynamic linear fixed effect model and by including all relevant variables we test both papers for omitted variable bias. We find that the individual effects of increased property rights and access to credit markets decreases and increases levels of overfishing respectively while trade openness had no effect. This points to a degree of omitted variable bias in Erhardt’s results as he concludes that increased trade openness decreases overfishing. The interaction terms of these variables are further explored through the use of marginal analysis.